2019
DOI: 10.1111/imr.12826
|View full text |Cite
|
Sign up to set email alerts
|

Microbial orchestra in juvenile idiopathic arthritis: Sounds of disarray?

Abstract: The role of the microbiota in multiple autoimmune diseases, including juvenile idiopathic arthritis (JIA) has earned substantial attention in the last 10 years. Increasing evidence suggests that the microbiota's link to JIA begins in early childhood, as early life events that influence the nature of the microbiota also appear to influence disease risk. In this review, we discuss these early life events including mode of delivery, infant feeding practice, antibiotics exposure, and other events and their impacts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 168 publications
0
16
0
Order By: Relevance
“…In addition, in JIA patients suffering from gastrointestinal symptoms, signs of altered mucosal immunity have been observed, such as inflammatory lesions in the intestine [44], ileal lymphonodular hyperplasia [45,46], and expression of HLA-DR in abnormal sites of the intestinal mucosa [45].Enthesitis-related arthritis (ERA) has been associated with certain intestinal microbial populations in a case-control study [47]. But other categories of JIA have also shown indications of alterations in the microbiota, as described by Arvonen et al [48]. The intestinal microbiota develops dramatically during the first years Table 3 Exposure to antibiotics in the uterus and during the early childhood of those children who later developed JIA, compared to controls from the general population…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in JIA patients suffering from gastrointestinal symptoms, signs of altered mucosal immunity have been observed, such as inflammatory lesions in the intestine [44], ileal lymphonodular hyperplasia [45,46], and expression of HLA-DR in abnormal sites of the intestinal mucosa [45].Enthesitis-related arthritis (ERA) has been associated with certain intestinal microbial populations in a case-control study [47]. But other categories of JIA have also shown indications of alterations in the microbiota, as described by Arvonen et al [48]. The intestinal microbiota develops dramatically during the first years Table 3 Exposure to antibiotics in the uterus and during the early childhood of those children who later developed JIA, compared to controls from the general population…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Faecalibacterium is involved in processes such as amino acid biosynthesis and starch and sugar degradation [48]. Studies have shown that increases in feces butyrate were found when the relative abundances of Lachnospiraceae, a family of digestive tract-associated bacteria [49], were increased [20]. In particular, the microbiota pro le appears to favor butyrate production, a common indicator of gut health, potentially through increases in the members of Lachnospiraceae, Faecalibacterium and Ruminococcaceae [20,45].…”
Section: Discussionmentioning
confidence: 99%
“…Although conceptually attractive, some therapies targeting IL-17A are efficacious in the joint but not vice versa, and the targeting of adhesion molecules such as α4β7 in IBD can lead to onset or flares of SpA (67). Recent studies in ethnically different patient populations, and especially in patients with HLA-B27, have demonstrated dysbiosis in patients with SpA (68)(69)(70)(71)(72)(73)(74)(75)(76). Such dysbiosis is highly dependent on the host's genetic background and/or environment, implicating an "ecological model of dysbiosis", with the effects of a multitude of microbes contributing all to the aberrant immunopathogenesis (77).…”
Section: Subclinical Gut Inflammation (Gut-joint Axis)mentioning
confidence: 99%